2018
DOI: 10.1016/j.immuni.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Mutation of Card14 Leads to Spontaneous Psoriasis-like Skin Inflammation through Enhanced Keratinocyte Response to IL-17A

Abstract: Genetic mutations of CARD14 (encoding CARMA2) are observed in psoriasis patients. Here we showed that Card14 and Card14 mice developed spontaneous psoriasis-like skin inflammation, which resulted from constitutively activated CARMA2 via self-aggregation leading to the enhanced activation of the IL-23-IL-17A cytokine axis. Card14 mice displayed attenuated skin inflammation in the imiquimod-induced psoriasis model due to impaired IL-17A signaling in keratinocytes. CARMA2, mainly expressed in keratinocytes, assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 38 publications
6
131
0
2
Order By: Relevance
“…Keratinocytes express both IL-17RA/IL-17RC and IL-17RA/IL-17RD, and the binding of IL-17A induces the transcription of differential gene sets [93]. Initial subcellular events in the ligation of IL-17RA/RC by IL-17A are the recruitment and activation of ACT1 encoded by the TRAF3IP2 gene, TRAF6 and CARMA2 complexes, and the downstream activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and MAPKs [93][94][95][96][97]. The ligation of IL-17RA/IL-17RC by IL-17A induces the activation of NF-κB, ERK, p38 MAPK, and JNK, while that of IL-17RA/IL-17-RD mainly activates p38 MAPK and JNK and barely affects NF-κB and ERK [93].…”
Section: Il-17a Signaling Systemmentioning
confidence: 99%
“…Keratinocytes express both IL-17RA/IL-17RC and IL-17RA/IL-17RD, and the binding of IL-17A induces the transcription of differential gene sets [93]. Initial subcellular events in the ligation of IL-17RA/RC by IL-17A are the recruitment and activation of ACT1 encoded by the TRAF3IP2 gene, TRAF6 and CARMA2 complexes, and the downstream activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and MAPKs [93][94][95][96][97]. The ligation of IL-17RA/IL-17RC by IL-17A induces the activation of NF-κB, ERK, p38 MAPK, and JNK, while that of IL-17RA/IL-17-RD mainly activates p38 MAPK and JNK and barely affects NF-κB and ERK [93].…”
Section: Il-17a Signaling Systemmentioning
confidence: 99%
“…A very recent study found that IL-17 and IL-22 promote keratinocyte stemness (Ekman et al, 2019). In two studies, it was shown that mice with a gain-of-function mutation of the card14 gene, a known risk locus for human psoriasis, developed spontaneous psoriasis-like skin inflammation triggered by IL-17 mostly derived from αβ T cells acting on keratinocytes (Mellett et al, 2018;Wang et al, 2018). This was mediated by intracellular CARMA2 accumulation and activation.…”
Section: Il-17 Immunitymentioning
confidence: 99%
“…We used MALT1 KO cells for this pathway evaluation since reconstitution of MALT1 does not induce any NF-κB activity on its own, whereas overexpression of Bcl10 or CARD10 leads to spontaneous NF-κB activation. In contrast, another suggested upstream activator of a CBM complex-dependent signaling pathways is the IL-17 receptor adaptor Act1 [69]. In our screening system, Act1 activated NF-κB independently of the CBM complex components ( Fig.…”
Section: Verification Of the Screening Tools For Pathway Analysesmentioning
confidence: 87%
“…For evaluation of GPCR components proposed to act upstream of CBMcomplex dependent signaling, we used Gα 12 -Q231L, Gα 13 -Q226L [101], and RhoA-Q63L (LMBP 04658) [102] expression plasmids. Also the IL-17 receptor adaptor Act1 (pEF-hCIKS) was evaluated as a potential upstream activator of CBM dependent signaling [69] by transient transfection in the KO model cells. For studies of CARD-CC heterocomplex formation with CARD14, a non-tagged CARD14 (LMBP 9863) clone was used [14].…”
Section: Card-cc and Activated Pkc Expression Plasmidsmentioning
confidence: 99%